Health economic evaluation of primary human papillomavirus screening in urban populations in China. (February 2021) - Keane, Adam; Shi, Ju-Fang; Simms, Kate T.; Liu, Yi-Jun; Lew, Jie-Bin; Mazariego, Carolyn; Yuill, Susan; Wu, Rui-Fang; Liu, Zhi-Hua; Zhao, Fang-Hui; Jeronimo, Jose; Canfell, Karen; et al.
Highlights: In 2018, the WHO issued a call to eliminate cervical cancer, with screening being a key component. We focused on screening evaluations for Shenzhen as an example of an urban city in China. Strategies were based on guidelines and trials using a well-validated model ( 'Policy1-Cervix' ). The most cost-effective strategy is HPV genotyping every 5−10 years, starting at age 25. This reduced ASR incidence and mortality by 56 % and 63 %, respectively. Abstract: Background: On Nov 17, 2020, WHO launched a global initiative to accelerate the elimination of cervical cancer through the implementation of HPV vaccination, cervical cancer screening and treatment for precancer and cancer. China has the largest burden of cervical cancer in the world, but only has a national cervical cancer screening program in rural areas since 2009. Here, we aimed to evaluate the effectiveness and cost-effectiveness of cervical cancer screening in urban China, using Shenzhen City as an example. Methods: We use an extensively validated platform ( 'Policy1-Cervix' ), calibrated to data from Shenzhen city and Guandong Province. We evaluated a range of strategies that have previously been implemented as pilot studies in China, or recommended as guidelines within China and globally, spanning primary HPV, cytology and co-testing strategies. We additionally considered alternate triaging methods, age ranges and screening intervals, resulting in 19 algorithms in total. Results: Of the 19 strategies considered, the most effective approach involved primary HPV testing. At 3- to 10-yearly intervals, primary HPV testing reduced the age-standardized cancer mortality rate by 37–71 %. The most cost-effective strategy was 5-yearly primary HPV testing with partial genotyping triage for ages 25−65, discharging to 10-yearly screening for low-risk women (ICER = US$7191/QALYS using 2018 costs; willingness-to-pay threshold<1xGDP [US$9771]). This strategy gave an incidence and mortality reduction of 56 % and 63 %, respectively. This remained the most cost-effective strategy under most conditions in sensitivity analysis. Conclusion: Primary HPV testing would be cost-effective in Shenzhen and could more than halve cervical cancer incidence rates to 6 per 100, 000 over the long term. In order to achieve rates below 4 per 100, 000, the elimination threshold set by the World Health Organization, vaccination will likely also be necessary.